2016
DOI: 10.1039/c5cp07854g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and enhanced photocatalytic CO2 reduction activity of graphene supported TiO2 nanocrystals with coexposed {001} and {101} facets

Abstract: It is known that the combination of TiO2 and graphene and the control of TiO2 crystal facets are both effective routes to improve the photocatalytic performance of TiO2. Here, we report the synthesis and the photocatalytic CO2 reduction performance of graphene supported TiO2 nanocrystals with coexposed {001} and {101} facets (G/TiO2-001/101). The combination of TiO2 and graphene enhanced the crystallinity of TiO2 single nanocrystals and obviously improved their dispersion on graphene. The "surface heterojuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 40 publications
(61 reference statements)
2
43
0
Order By: Relevance
“…Particularly, some physicochemical properties are connected closely with the surface atomic configuration and the exposure of the specific facets. There are three fundamental low-index facets exposed generally in anatase TiO 2 nanocrystals: (001), (010) and (101) facets, and their average surface energies reported in the literature are 0.90, 0.53 and 0.44 J/m 2 , respectively [14][15][16]. Higher surface energy of (001) facets is more efficient for dissociative adsorption of reactant molecules compared with (010) and (101) facets, which has the high density of active unsaturated coordination Ti atoms and the presence of enlarged Ti-O-Ti bond angles on the surface [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, some physicochemical properties are connected closely with the surface atomic configuration and the exposure of the specific facets. There are three fundamental low-index facets exposed generally in anatase TiO 2 nanocrystals: (001), (010) and (101) facets, and their average surface energies reported in the literature are 0.90, 0.53 and 0.44 J/m 2 , respectively [14][15][16]. Higher surface energy of (001) facets is more efficient for dissociative adsorption of reactant molecules compared with (010) and (101) facets, which has the high density of active unsaturated coordination Ti atoms and the presence of enlarged Ti-O-Ti bond angles on the surface [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, TiO 2 materials are the most widely investigated photocatalysts due to their high stability, low cost and non-toxic nature [11][12][13]. Pure TiO 2 and TiO 2based composites of various configurations, composition and morphology at the nanoscale have been synthesized and applied in CO 2 photoreduction [14][15][16][17][18]. Overall, studies on TiO 2 have shown that photocatalytic activity is drastically affected by the exposed TiO 2 facets.…”
Section: Introductionmentioning
confidence: 99%
“…These merits contribute the possibility of various photocatalytic reactions to continue under ultraviolet (UV) illumination 3 . Many endeavors have been dedicated to enhance the photoactivity of TiO 2 based nanomaterials, such as defect engineering 4 , 5 , crystal facets regulation, the surface/interface control 6 , 7 , and the complex structures 8 . Chen et al .…”
Section: Introductionmentioning
confidence: 99%